The Effect of Financial Ratios on Financial Distress in Matahari Department Store Companies listed on the Indonesia Stock Exchange for the 2016-2020 period - Permita Dwi Indah Sari; Evaliati Amaniyah (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
The purpose of this study was to determine the ef ect of liquidity, leverage, profitability and activity on financial distress at Matahari Department Store companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This research was conducted descriptively and quantitatively. This research was processed using SPSS IBM 25. This research was conducted by analyzing financial statements, based on the application using the Z-score method. Descriptive data analysis techniques, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study are partially liquidity and leverage ratios have a negative and insignificant ef ect on financial distress, profitability ratios have a positive and insignificant ef ect on financial distress, while the activity ratio has a positive and significant ef ect on financial distress